1990
DOI: 10.1172/jci114823
|View full text |Cite
|
Sign up to set email alerts
|

Apical membrane limits urea permeation across the rat inner medullary collecting duct.

Abstract: Urea diffuses across the terminal inner medullary collecting duct (IMCD) via a facilitated transport pathway. To examine the mechanism of transcellular urea transport, membrane-apparent urea (Pme) and osmotic water (Pf) permeabilities of IMCD cells were measured by quantitative light microscopy in isolated IMCD-2 tubules perfused in the absence of vasopressin. Basolateral membrane Pf, determined by addition of raffinose to the bath, was 69 ,um/s. Basolateral membrane Pri, determined by substituting urea for ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 31 publications
4
21
0
Order By: Relevance
“…Fig. 4A shows rapid osmotically induced volume changes in cortical collecting ducts from wild-type mice, with a half-time (t 1͞2 ) for osmotic equilibration of 1.09 Ϯ 0.09 s, a few times slower than the system exchange time of Ϸ0.3 s. This rapid equilibration is comparable to that measured in microperfused collecting ducts from rabbit (26) and rat (27,28) in which cell volume was deduced by tubule imaging, and perfusate exchange was accomplished in Ͻ0.1 s. Osmotic equilibration of collecting ducts from AQP3-knockout mice was significantly slower: 2.69 Ϯ 0.1 s. Because of the finite solution exchange time in our system that might underestimate the rate in tubules from wild-type mice, it is concluded that AQP3 deletion produces at least a 3-fold decrease in water permeability of the basolateral membrane of cortical collecting duct. We did not compute absolute P f values because of uncertainties in the basolateral membrane surface area exposed to the perfusate.…”
Section: Resultsmentioning
confidence: 56%
“…Fig. 4A shows rapid osmotically induced volume changes in cortical collecting ducts from wild-type mice, with a half-time (t 1͞2 ) for osmotic equilibration of 1.09 Ϯ 0.09 s, a few times slower than the system exchange time of Ϸ0.3 s. This rapid equilibration is comparable to that measured in microperfused collecting ducts from rabbit (26) and rat (27,28) in which cell volume was deduced by tubule imaging, and perfusate exchange was accomplished in Ͻ0.1 s. Osmotic equilibration of collecting ducts from AQP3-knockout mice was significantly slower: 2.69 Ϯ 0.1 s. Because of the finite solution exchange time in our system that might underestimate the rate in tubules from wild-type mice, it is concluded that AQP3 deletion produces at least a 3-fold decrease in water permeability of the basolateral membrane of cortical collecting duct. We did not compute absolute P f values because of uncertainties in the basolateral membrane surface area exposed to the perfusate.…”
Section: Resultsmentioning
confidence: 56%
“…3) demonstrated a predominant apical localization of RUT in IMCD cells. The apical plasma membrane is rate-limiting for overall transepithelial urea transport and manifests a large increase in urea permeability in response to vasopressin (9). Our immunolocalization results therefore support the view that RUT is the "vasopressin-regulated urea transporter" of the apical plasma membrane as suggested previously from (i) the similarity between the urea transport properties of intact collecting ducts and Xenopus oocytes after injection of RUT cRNA (14) and (ii) the high level of expression of RUT mRNA in the IMCD (14).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological studies in isolated perfused tubules have demonstrated that this urea transport pathway is inhibitable by phloretin and structural analogs of urea (6), and is saturable (7), providing strong evidence for the presence of a facilitated urea transporter in IMCD cells (8). Although urea transport across both apical and basolateral plasma membranes of IMCD cells appears to be mediated by phloretin-sensitive urea transporters (6,9), urea transport across the apical plasma membrane is rate-limiting for overall transepithelial urea transport and is regulated by vasopressin (9). The mechanism by which vasopressin increases urea transport across the apical plasma membrane of the IMCD has not been investigated.…”
mentioning
confidence: 99%
“…Therefore, the accumulation of UT in the apical plasma membrane of the collecting tubule is important and most likely functions as a rate-limiting step for urea reabsorption in the houndshark kidney. In the mammalian kidney, the apical plasma membrane of IMCD was found to be the rate-limiting membrane for overall transepithelial transport of water and urea (105). Accumulation of the UT-A1 to the apical plasma membrane is a key step for the regulation of urea transport in the IMCD (64).…”
Section: Urea Retention In the Kidney: Urea Transportermentioning
confidence: 99%